Kepemimpinan Perempuan dalam Lembaga Pendidikan Islam (Studi Kasus di Pondok Pesantren Syaikh Zainuddin NW Anjani) - Hesti Dina Aulia; Yudin Citriadin; Muhammad Thohri (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
Leadership is the act of a leader in achieving educational goals. Its main action affects other people. In this study, researchers focused on three things, namely: (1) What is the policy-making strategy for women leaders in Islamic education institutions at MAK Hamzanwadi II? (2) What is the teacher's perception of women's leadership at MAK Hamzanwadi II? (3) What are the obstacles to women's leadership in Islamic educational institutions at MAK Hamzanwadi II?. The research method used is a qualitative method of case study research. Data collection techniques through observation, interviews and documentation. Data analysis techniques use data reduction, data condensation, data presentation, and verification. Test the validity of the data using credibility, dependability, confirmability, and transferability. The results of this study are (1) Leadership Policy Making Strategy at MAK Hamzanwadi II, namely implementing a decision-making strategy through initial identification of problem parts, formulation of problem solving objectives, and determination of criteria for selecting alternative solutions which become a set of decisions or policies. Decision making efforts are carried out by inviting the presence of the teacher council in a special meeting then explaining an issue related to the decision to be taken. (2) The teacher's perception of women's leadership at MAK Hamzanwadi II is that they have been accepted as figures who have managerial abilities and are nurturing. Institutional progress received affirmation from its subordinates as a form of emancipatory awareness strengthened by religious awareness. (3) Obstacles to female leaders in Islamic education institutions are firstly personal barriers based on perceptual barriers that arise from feelings of inappropriateness as leaders. The two relational barriers are in the form of communication barriers both in understanding the message and in the policy outreach strategy.